The Impact of Executive Information Systems on Organizational Design, Intelligence, and Decision Making - Leidner, Dorothy E.; Elam, Joyce J. (Organization Science, 1995)
Managerial decision making is regarded as among the most important functions of senior managers. The presence of easily accessible, reliable information contributes to effective decision making. Sources of information may be oral, written, or computer-based. The computer-based information sources remain the least studied in the context of executive decision making because executives have tended to use other managers and their own intuition as their primary information sources. Recently though, computer-based information systems directly tailored for use by executives have begun to be implemented within organizations. Such systems, referred to as Executive Information Systems, may help executives make faster and higher quality decisions, an increasingly important requirement for executives given such trends as globalization and heightened competition. This study uses survey responses of 91 high level managers to empirically examine the relationship of executive information system use by managers with decision making speed, problem identification speed, information availability, and the involvement of subordinates in decision making. The study found that when used frequently and over time, executive information systems are positively related to perceived problem identification and decision making speed for senior and middle managers. Whether such effects lead to higher quality decisions are topics for further study. In addition, the frequency of use of executive information systems is shown to be related to a perceived increase in information availability although the length of time the system is in use is not related to perceived information availability. This suggests that the information needs of senior and middle managers is malleable and systems designed to support the decision making of managers need to be flexible to adapt to changing information needs. Lastly, the study found that the use of executive information systems does not reduce the reliance of senior or middle managers on their subordinates to help in decision making. This may be because the involvement of subordinates does not necessarily connote a consistent positive or negative behavior among American managers, whereas speed and information are consistently considered as positive. The implications of the results for a previously developed theory of the effects of advanced information technology on organizational design, intelligence, and decision making are discussed.